SISTEM PAKAR MENDIAGNOSA PENYAKIT VAS, KULITIS MENGGUNAKAN METODE VARIABLE CENTERED INTELLIGENT RULE SYSTEM (VCIRS) - Susanti, Pipi; Hasibuan, Nelly Astuti; Ulfa, Kurnia (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
At this time the use of computer device technology has developed rapidly and the community. Most people use it not only for commercial purposes, but also to get information on disease detection quickly and efficiently with a computer-based application that can help the general public to find out the causes and symptoms of the disease. for that, a system is needed to imitate the expertise of an expert in answering questions and solving problems in accordance with the knowledge of an expert who is entered into a computer system. The development of artificial intelligence technology that has occurred has made it possible for expert systems to be applied to detect disease using programming languages. One of them is in providing information about various problems, especially Vasculitis. The expert system method used is a Variable Centered Intelligent Rule System (VCIRS) used to handle diagnosing vasculitis. With the facilities provided for users and administrators, allowing both users and administrators to use this system according to their individual needs. Users are given ease in knowing information about Vasculitis disease, its causes and deterrents. This expert system is created by using Microsoft Visual Basic 2008 Programming Language.Keywords: Expert System, Variable Centered Intelligent Rule System (VCIRS), Vasculitis